Classification and spatial characteristics of different development stages in China: Evidence from the contribution rate of production factors - Zijie Li; Xiangnan Liu; Lingfeng Xu; Qun Wu (PLoS ONE, 2025)
This paper aims to reveal the changing characteristics of the contribution rates of different production factors in China since the reform and opening up from two dimensions: stage and space. The study used national data from 1978 to 2021 and provincial data from 2000 to 2020, combined with methods such as C-D production function and spatial econometrics for analysis. Research has found that: (1) In terms of stage characteristics, during the structural adjustment stage (1978–1998), economic growth mainly relies on capital and labor input, and the contribution rate of land factors gradually decreases. During the high-speed development stage (1998–2012), the contribution rate of technological factors gradually increased, while the contribution rate of land factors remained relatively stable. In the stage of high-quality development (2012 present), the contribution rate of technological factors continued to rise and become the dominant factor, while the contribution rate of land factors has decreased to a lower level. (2) Regarding spatial characteristics, the spatial econometric model reveals significant spatial agglomeration characteristics of capital and labor, and land factors positively affect local and neighboring economic growth. From 2000 to 2020, the contribution rate of capital factors in various provinces showed a difference of "low in the east and high in the west," which decreased year by year. The contribution rates of labor and land factors have declined to low levels in all provinces; The contribution rate of technological elements has significantly increased, with a higher contribution rate in the southeast region; High-quality development progress in each province can be identified based on the contribution rates of different production factors. The research findings help to understand the impact of varying production factors on economic development at a temporal and spatial scale and provide a scientific basis for achieving a high-quality development pattern of rational allocation of factors and regional coordinated development.